A kind of heat-sensitive material for ultra-fine continuous thermocouple
By using a six-component thermal-sensitive material designed, ultra-fine continuous thermocouples with small diameter and small bending radius were prepared, which solved the problems of poor temperature measurement accuracy and large diameter bending radius in the prior art, and achieved high-precision temperature monitoring of new energy vehicle batteries.
Patent Information
- Application Number
- CN202311853441.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-12-29
AI Technical Summary
The existing continuous thermocouples have poor temperature measurement accuracy below 200°C, large diameter and large bending radius, making it difficult to meet the temperature monitoring needs of new energy vehicle batteries.
Thermal-sensitive material with a six-component design is adopted to improve the stability of the thermosensitive medium through the synergistic effect of multiple components and reduce the reaction with the K-type thermocouple wire, thereby preparing ultrafine continuous thermocouples with small diameter and small bending radius.
High-precision temperature measurement is achieved within the diameter of 0.5mm~1.0mm and the bending radius of 1mm~10mm. The temperature measurement range is normal temperature~800℃ and the accuracy is ±5℃. It is suitable for temperature monitoring of automotive lithium batteries.
Smart Images

Figure BDA0004641599970000051 
Figure BDA0004641599970000061 
Figure BDA0004641599970000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of temperature sensors, and in particular relates to a thermosensitive material for an ultra-fine continuous thermocouple. Background Art
[0002] The temperature of new energy vehicle batteries will rise during operation. If the battery is operated at high temperature, it is easy to age and the electrical performance will decline. In serious cases, safety accidents may even occur. Therefore, it is very necessary to monitor the temperature of electric vehicle batteries. At present, most of the temperature sensors used for temperature measurement of new energy vehicle batteries are point temperature sensors. Point temperature sensors are in contact with the surface of the battery. If there are few point temperature sensors, there are monitoring loopholes. If there are many point temperature sensors, the sensor harness will occupy a large space. Therefore, there is an urgent need for a low-cost, high-reliability wide-area temperature sensor.
[0003] Continuous thermocouples are arranged in a plane, which can achieve wide-area temperature measurement. It is a sensor used to measure the hottest temperature along the longitudinal space of the thermocouple. It is mainly composed of three parts: thermocouple, insulation material, and protection tube. The thermocouple is a pair of parallel thermocouples separated by a certain distance. The insulation material tightly filled between the thermocouples is a thermistor material with a negative temperature coefficient (NTC) made by a special process. The resistance is very large at low temperatures, and the resistance decreases sharply with the increase of temperature. When the temperature at any point on the length of the continuous thermocouple is higher than the temperature of other parts, the insulation resistance between the thermocouples at that point decreases, resulting in a "temporary" thermocouple measurement end. At this time, it constitutes a conventional thermocouple. As long as the thermoelectric potential is measured at the reference end of the thermocouple, the temperature at the junction ("temporary" hot junction) can be determined. The current continuous thermocouples are mainly used in the fields of petroleum, chemical industry, etc., but these continuous thermocouples have the following problems: poor temperature measurement accuracy below 200°C, large diameter, diameter between 2.5 and 3.5 mm, and large bending radius. Therefore, how to solve the above problems has become the focus of people's research. Summary of the invention
[0004] The purpose of the present application is to provide a thermosensitive material for an ultrafine continuous thermocouple, wherein the material adopts a six-component design, and the synergistic effect of multiple components is used to improve the stability of the thermosensitive medium. This six-component design can reduce the reaction between the thermosensitive medium and the K-type thermocouple wire, and ensure the temperature measurement accuracy of the K-type thermocouple. The thermosensitive material of the present invention can be used to prepare an ultrafine continuous thermocouple, which has a small diameter between 0.5 mm and 1.0 mm, can be bent arbitrarily, and has a minimum bending radius between 1 mm and 10 mm. It has a temperature sensing function at any point, can measure the temperature of the highest temperature point in the field to be measured, and has a temperature measurement range between room temperature and 800°C, with a temperature measurement accuracy of ±5°C. The ultrafine continuous thermocouple can be used to measure the temperature of automotive lithium batteries. Due to its small diameter and small bending radius, it is easier to fit the lithium battery and can be wrapped around the surface of the automotive lithium battery to measure its temperature without any temperature measurement blind spots. The ultrafine continuous thermocouple is vibration-resistant, corrosion-resistant, easy to install, low-cost, easy to adjust, and can set over-temperature alarm limits and temperature rise rate alarm limits.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] The weight percentage of each component of the heat-sensitive material for ultrafine continuous thermocouple is: 10-15% of aluminum oxide, 15-18% of ferric oxide, 15-18% of chromium oxide, 20-24% of manganese carbonate, 5-10% of cobalt oxide, and the balance is magnesium oxide.
[0007] A better technical solution is that the weight percentage of each component of the material is:
[0008] Aluminum oxide 10-13%, ferric oxide 15-16%, chromium oxide 15-16%, manganese carbonate 20-22%, cobalt oxide 5-8%, and the balance is magnesium oxide.
[0009] Aluminum oxide 13-15%, iron oxide 16-18%, chromium oxide 16-18%, manganese carbonate 22-24%, cobalt oxide 8-10%, and the balance is magnesium oxide.
[0010] Application of the above-mentioned thermosensitive material in the preparation of ultra-fine continuous thermocouples.
[0011] The method for preparing the thermosensitive material includes the following steps:
[0012] 1) Weigh magnesium oxide, aluminum oxide, ferric oxide, chromium oxide, manganese carbonate, and cobaltous oxide according to weight ratio;
[0013] 2) Place the above compounds in a ball mill tube, add an appropriate amount of alcohol, and ball mill at a speed of 100r / min to 300r / min for 10 to 20h, then take out and dry;
[0014] 3) Sintering the ball-milled powder at 1200°C to 1300°C for 3 to 5 hours;
[0015] 4) ball milling the sintered powder at a speed of 100 r / min to 150 r / min for 2 to 3 hours;
[0016] 5) The prepared heat-sensitive material powder is fully mixed with 20-25 parts of water and 0.2-0.5 parts of methyl cellulose, kneaded into a paste, and extruded into an outer diameter of The porcelain column is dried and set aside;
[0017] 6) Sinter the dried porcelain column at 1200-1250℃ for 3h.
[0018] The preparation of ultra-fine continuous thermocouples is as follows:
[0019] 1) Cut the K-type thermocouple wires in pairs, and the cutting length is 1.5 times the length of the stainless steel outer tube;
[0020] 2) Insert the thermocouple wire into the thermosensitive material porcelain column for assembly, and then install it into the stainless steel outer tube;
[0021] 3) The assembled assembly is drawn to 0.5 mm to 1.0 mm using a wire drawing machine.
[0022] The functions of each element in the material of the present invention are as follows:
[0023] Magnesium oxide: The content of magnesium oxide can change the temperature coefficient of resistance. Increasing the content of magnesium oxide can increase the temperature coefficient of resistance and improve the sensitivity of ultra-fine continuous thermocouples. Other compounds react with magnesium oxide to form composite oxide thermistor ceramic materials. This composite oxide thermistor ceramic material has a negative temperature coefficient of resistance. Except that aluminum oxide is an insulating phase that increases resistance, the other compounds have similar effects, all of which provide a conductive phase. In addition, the doping of multiple compounds has a synergistic effect that can improve the stability of the material.
[0024] Manganese (Mn): It is the core element of thermosensitive materials. When the content of Mn is low in thermosensitive materials, the resistivity will decrease as the content of Mn increases. This is because the increase of Mn makes the B-position Mn 4+ / Mn 3+ Ion pairing increases Mn 4+ / Mn 3+ Ion pairs exchange electrons to promote conductivity, but when the Mn content reaches a certain value, the resistivity will increase instead. This is because too much Mn will cause the lattice structure to be distorted, from a cubic spinel structure to a tetragonal phase, resulting in an increase in resistivity.
[0025] Cobalt (Co): Cobalt exists in divalent and trivalent states and is a variable valence element. It is generally believed that the following conductive mechanisms exist in thermosensitive materials:
[0026]
[0027] However, the Co element is not as easy to change valence as the Mn element. Therefore, the addition of the Co element can improve the conductivity, but it is not as critical as the Mn element.
[0028] Iron (Fe) element: Fe element has similar properties to Co element, and has divalent and trivalent properties. Fe element can partially replace Co element, which has a relatively high cost. The conductivity of the thermosensitive material will decrease as the amount of Fe element replaced increases. In addition, the addition of Fe element can improve the thermal stability of the thermosensitive material.
[0029] Chromium (Cr) element: It is beneficial to improve the temperature coefficient of resistance of thermistor materials. At the same time, Cr element can improve the aging stability of thermistor materials.
[0030] Aluminum (Al) element: The element is a non-volatile element. The addition of Al element can reduce the carrier concentration in the material and increase the resistance of thermistor material. At the same time, Al element is beneficial to improve the high temperature stability of thermistor material.
[0031] The addition of Al and Cr elements helps to improve the room temperature resistance of the thermosensitive material, ensure the resistance requirements between the ultra-fine continuous thermocouple core wires, and ensure the temperature measurement accuracy below 200°C. At the same time, the multi-component thermosensitive material has a very high configuration entropy, which helps to improve the stability of the thermosensitive material and reduce its reaction with the core wire.
[0032] Due to the adoption of the above technical solution, the present invention has the following advantages:
[0033] 1) The thermosensitive material of the present invention adopts a six-component design, which improves the stability of the thermosensitive medium through the synergistic effect of multiple components. This design can reduce the reaction between the thermosensitive medium and the K-type thermocouple wire and ensure the temperature measurement accuracy of the K-type thermocouple.
[0034] 2) The thermosensitive material of the present invention can be used to prepare ultra-fine continuous thermocouples. The thermocouple has a small diameter of only 0.5 mm to 1 mm and a bending radius of 1 mm to 10 mm. It can sense temperature at any point and measure the highest temperature along the line.
[0035] 3) The ultra-fine continuous thermocouple can be used to measure the temperature of the surface of automotive lithium batteries. Due to its small diameter and small bending radius, it is easy to install in a compact lithium battery. It can also be wrapped around the surface of the lithium battery to measure its temperature without blind spots.
[0036] 4) The ultra-fine continuous thermocouple can be bent arbitrarily, is vibration-resistant, corrosion-resistant, easy to install, and has low cost. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0038] All reagents described in this example are commercial analytical grade reagents.
[0039] Example 1
[0040] Weigh: 75 grams of magnesium oxide, 75 grams of aluminum oxide, 90 grams of ferric oxide, 90 grams of chromium oxide, 120 grams of manganese carbonate, 50 grams of cobaltous oxide, put into a 500ml ball mill, add 200ml of alcohol, ball mill at a speed of 300r / min for 10 hours, put the mixed slurry into an oven and dry for 24 hours to obtain a mixed powder. Then sinter at 1200℃ in a muffle furnace for 3 hours, and then ball mill the sintered material at a speed of 150r / min for 3 hours to obtain a thermosensitive material powder. Mix the heat medium powder with water in a ratio of 100:20, add 0.5 parts of methyl cellulose, knead it into a mud, and extrude it into an outer diameter through a special porcelain column extruder. The porcelain column is placed in the shade at room temperature for 5 days and sintered in a muffle furnace at 1200℃ for 3h. The K-type thermocouple wire is assembled with the sintered porcelain column and the stainless steel outer tube, and is drawn into a 0.5mm ultra-fine continuous thermocouple through a drawing process. The digital multimeter is used to test its room temperature resistance to reach 50MΩ·m. The ultra-fine continuous thermocouple is coiled into a circle and placed in a high-temperature test box, with one end exposed to the test box, and the positive and negative poles of the core wire are connected to the reference end of the ice bottle. The multimeter is used to read its room temperature ~800℃ potential, and the test temperature is obtained by comparing it with the K-type thermocouple graduation table. The results are shown in Table 1, and the temperature measurement accuracy reaches ±5℃.
[0041] Table 1 Temperature measurement accuracy of Example 1
[0042]
[0043] Example 2
[0044] Weigh: 175g magnesium oxide, 50g aluminum oxide, 75g ferric oxide, 75g chromium oxide, 100g manganese carbonate, 25g cobalt oxide, put into a 500ml ball mill, add 200ml alcohol, ball mill at 100r / min for 20h, put the mixed slurry into an oven and dry for 24h to obtain a mixed powder. Then sinter at 1200℃ for 3h in a muffle furnace, and then ball mill the sintered material at 150r / min for 3h to obtain a thermosensitive material powder. Mix the heat medium powder with water in a ratio of 100:20, add 0.5 parts of methyl cellulose, knead it into a mud, and extrude it into an outer diameter through a special porcelain column extruder. The porcelain column was placed in the shade at room temperature for 5 days and then sintered in a muffle furnace at 1200℃ for 3h. The K-type thermocouple wire was assembled with the sintered porcelain column and the stainless steel outer tube, and then drawn into a 1.0mm ultra-fine continuous thermocouple through a drawing process. The room temperature resistance was tested with a digital multimeter to reach 500MΩ·m. The ultra-fine continuous thermocouple was coiled into a circle and placed in a high-temperature test box, with one end exposed to the test box, and the positive and negative poles of the core wire were connected to the reference end of the ice bottle. The electric potential at room temperature to 800℃ was read with a multimeter, and the test temperature was obtained by comparing it with the K-type thermocouple graduation table. The results are shown in Table 2, and the temperature measurement accuracy reached ±5℃.
[0045] Table 2 Temperature measurement accuracy of Example 2
[0046]
[0047] Example 3
[0048] Weigh: 125g magnesium oxide, 65g aluminum oxide, 80g ferric oxide, 80g chromium oxide, 110g manganese carbonate, 40g cobalt oxide, add 200ml alcohol, ball mill at 200r / min for 15h, sinter at 1250℃ for 5h, make a porcelain column after ball milling and sinter at 1200℃ for 3h. After assembling the K-type thermocouple wire with the porcelain column and the stainless steel outer tube, pull it into a 0.8mm ultrafine continuous thermocouple. Its room temperature resistance reaches 160MΩ·m, and the temperature measurement accuracy reaches ±5℃ in the range of room temperature to 800℃. Put it in a 500ml ball milling jar, add 200ml alcohol, ball mill at 200r / min for 15h, put the mixed slurry into an oven and dry it for 24h to obtain a mixed powder. Then sinter it at 1200℃ for 3h in a muffle furnace, and then ball mill the sintered material at 150r / min for 3h to obtain a thermosensitive material powder. Mix the heat medium powder and water in a ratio of 100:20, add 0.5 parts of methyl cellulose, knead into a mud, and extrude it into an outer diameter through a special porcelain column extruder. The porcelain column was placed in the shade at room temperature for 5 days to dry, and then placed in a muffle furnace and sintered at 1200℃ for 3h. The K-type thermocouple wire was assembled with the sintered porcelain column and the stainless steel outer tube, and then drawn into a 0.8mm ultra-fine continuous thermocouple through a drawing process. The room temperature resistance was tested with a digital multimeter to reach 160MΩ·m. The ultra-fine continuous thermocouple was coiled into a circle and placed in a high-temperature test box, with one end exposed to the test box. The room temperature ~800℃ potential was tested according to the K-type thermocouple test method. The results are shown in Table 3, and the temperature measurement accuracy reached ±5℃.
[0049] Table 3 Temperature measurement accuracy of Example 3
[0050]
Claims
1. An application of a thermosensitive material for ultrafine continuous thermocouple in the preparation of ultrafine continuous thermocouple, characterized in that: The preparation method of the ultra-fine continuous thermocouple heat-sensitive material comprises the following steps: 1) Weigh the raw materials according to the weight ratio; The weight percentage of each component of the raw material is: 10-15% aluminum oxide, 15-18% iron oxide, 15-18% chromium oxide, 20-24% manganese carbonate, 5-10% cobalt oxide, and the balance is magnesium oxide; 2) Put the above raw materials into a ball mill, add appropriate amount of alcohol, ball mill at a speed of 100r / min~300r / min for 10~20h, take out and dry; 3) Sinter the ball-milled powder at 1200℃~1300℃ for 3~5h; 4) Ball mill the sintered powder at a speed of 100 r / min to 150 r / min for 2 to 3 hours to obtain a thermosensitive material powder; 5) The prepared heat-sensitive material powder is fully mixed with 20-25 parts of water and 0.2-0.5 parts of methyl cellulose, kneaded into a mud-like state, extruded into a porcelain column by a porcelain column extruder, and dried for later use; 6) Sinter the dried porcelain column at 1200-1250°C for 3 hours to obtain the thermistor material for ultrafine continuous thermocouple.
2. The use of a thermosensitive material for ultrafine continuous thermocouple according to claim 1 in the preparation of ultrafine continuous thermocouple, characterized in that: The weight percentage of each component of the raw material is: 10-13% aluminum oxide, 15-16% iron oxide, 15-16% chromium oxide, 20-22% manganese carbonate, 5-8% cobalt oxide, and the balance is magnesium oxide.
3. The use of a thermosensitive material for ultrafine continuous thermocouple according to claim 1 in the preparation of ultrafine continuous thermocouple, characterized in that: The weight percentage of each component of the raw material is: 13-15% aluminum oxide, 16-18% iron oxide, 16-18% chromium oxide, 22-24% manganese carbonate, 8-10% cobalt oxide, and the balance is magnesium oxide.
Citation Information
Patent Citations
High-entropy NTC thermistor ceramic material and preparation method thereof
CN112624740A